Strategi Manajemen Organisasi Pendidikan dalam Menghadapi Tantangan Globalisasi - Citra Dewi Utami; Ely Armayani; Indri Ariani; Raisya Nafilah Lubis; Salsabila Henrita Sari; Yohana Fransisca; Yulia Sri Hikma Hutasuhut; Inom Nasution (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to identify and analyze management strategies of educational organizations in facing the challenges of globalization, focusing on the enhancement of teacher and educational staff competencies, integration of technology in teaching and learning processes, and adaptation to changes in international educational policies. The research methodology employed is a literature review, involving an examination of literature from various sources such as academic journals, books, and research reports. The findings indicate that enhancing teacher competencies through continuous training and international collaboration is crucial in creating an interactive and relevant learning environment. The integration of technology in education allows for more flexible and personalized learning experiences, as well as broad access to global educational resources. Additionally, adaptation to international educational policies, including curriculum adjustments and evaluation standards, ensures the relevance and competitiveness of the education provided. These strategies are interconnected and mutually reinforcing, creating a dynamic and responsive educational system to global changes, thus preparing students to compete at the international level.